1997
DOI: 10.1093/ageing/26.2.147
|View full text |Cite
|
Sign up to set email alerts
|

CYP2D6, NAT2 and CYP2EI genetic polymorphisms in nonagenarians

Abstract: longevity does not seem to be related to any special configuration of these three polymorphic traits. Comparisons with younger controls may be adequate when studying the distribution of these polymorphisms in diseases affecting old people. No genetically determined differences in the activation of drugs metabolized by these enzymes are to be expected in very old people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“…We found that the level of our GlycoAgeTest This difference could be partly due to common lifestyle between Belgium and Italy, and genetic polymorphisms (Melzer, 2008;Agundez et al, 1997;Melzer et al, 2007). It was recently documented that plasma N-glycans is affected by age, body mass index, plasma lipid profiles and smoking (Knezevic et al, 2010).…”
Section: Discussionmentioning
confidence: 72%
“…We found that the level of our GlycoAgeTest This difference could be partly due to common lifestyle between Belgium and Italy, and genetic polymorphisms (Melzer, 2008;Agundez et al, 1997;Melzer et al, 2007). It was recently documented that plasma N-glycans is affected by age, body mass index, plasma lipid profiles and smoking (Knezevic et al, 2010).…”
Section: Discussionmentioning
confidence: 72%
“…The CYP2E1 gene had shown to encode enzyme that is involved in the metabolism of several drugs such as paracetamol, chlorzoxazone and ethanol (Agundez et al, 1997). Investigators reported that Japanese (Kim et al, 1996) had a lower oral clearance of the chlorzoxazone (in vivo probe) when compared with Caucasians.…”
Section: Resultsmentioning
confidence: 99%
“…Controls were members of faculty and hospital staff and students from the same geographical distributions as the cases. Age differences between cases and controls were not considered to influence the study because previous data showed no correlation between genotype and age [19,20]. Institutional Review Board approved the research, and informed consents were obtained from all patients and controls.…”
Section: Subjects and Methods Cases And Controlsmentioning
confidence: 99%